Landwirtschaft im nationalen Wettbewerb und die Rolle des Bodenmarktes - Alfons Balmann (Wirtschaftsdienst, 2024)
– German agriculture exhibits persistent income problems. While larger farms are on average quite profitable, this is consistently not true for the majority of part-time and small- and medium-sized family farms. These farms are particularly prominent in the southern and western parts of Germany while larger family and corporate farms dominate the north and the east. Competition among farms is fierce on land markets. Particularly regions with smaller farms exhibit high land prices, often higher than the Ricardian land rents. This market disequilibria as well as the persistence of income deficits for small farms can be attributed to agricultural subsidies, tax benefits and legal privileges.
Keywords: Q12; Q15; Q18; 330